Effect of anatomical differences and intraocular lens design on negative dysphotopsia. Issue 12 (6th December 2022) - van Vught, Luc; Que, Ivo; Luyten, Gregorius P.M.; Beenakker, Jan-Willem M.
Abstract : Ray-tracing simulations show that anatomical differences between patients with and without negative dysphotopsia have a strong, up to 18%, effect on the severity of the complaint. Abstract : Purpose: To assess the effect of ocular anatomy and intraocular lens (IOL) design on negative dysphotopsia (ND). Setting: Department of Ophthalmology, Leiden University Medical Center, Leiden, the Netherlands. Design: Ray-tracing study based on clinical data. Methods: Ray-tracing simulations were performed to assess the effect of anatomical differences and differences in IOL design on the peripheral retinal illumination. To that end, eye models that incorporate clinically measured anatomical differences between eyes of patients with ND and eyes of pseudophakic controls were created. The anatomical differences included pupil size, pupil centration, and iris tilt. The simulations were performed with different IOL designs, including a simple biconvex IOL design and a more complex clinical IOL design with a convex–concave anterior surface. Both IOL designs were analyzed using a clear edge and a frosted edge. As ND is generally considered to be caused by a discontinuity in peripheral retinal illumination, this illumination profile was determined for each eye model and the severity of the discontinuity was compared between eye models. Results: The peripheral retinal illumination consistently showed a more severe discontinuity in illumination with ND-specific anatomy. This difference was the least pronounced, 8%, with the frosted edge clinical IOL and the most pronounced, 18%, with the clear edge biconvex IOL. Conclusions: These results show that small differences in the ocular anatomy or IOL design affect the peripheral retinal illumination. Therewith, they can increase the severity of ND by up to 18%.